PEMBELAJARAN SASTRA APRESIATIF DENGAN REKREASI-RESPONSI-REDESKRIPSI DALAM PERSPEKTIF KBK (Kajian Linguistik dan Sastra, 2006)
The learning of literature in secondary, high, or vocational schools seems less appreciative. The main reason lies in the competency of literature teachers in ap- preciating literature beside the teaching for the target of curriculum and the Na- tional Grade Evaluation. The problem is show is the learning of literature viewed from Curriculum-Based-Competency (CBC) ? Which approach is appropriate for the appreciative learning of literature? A recreation-response-and-redescription model of learning literature using reception approach can be used as an alternative to realize a more appreciative learning of literature becauase it is in line with the CBC paradigm in stressing on the empowerment of studentsâ competency. To make such an empowering concrete, literature teachers may enhance their competency and commit on improving literary appreciation within their process of teaching and learning literature. In short, a change for a new paradigm for literature teach- ers is needed in the course of literature learning to have the spirit of CBC.Â Key words:Â  Â Pembelajaran Sastra Apresiatif, rekreasi-responsi-redeskeripsi, KBK atauCBC.Â Â Â